Kualitas Tidur dan Tekanana Darah pada Ibu Hamil - Rahayu, Siska; Bahriyah, Fitriyani; Rahayu, Restianingsih Putri (Poltekkes Kemenkes Riau Under Health Ministry Republik Indonesia, 2022)
Maternal Mortality Rate (MMR) is one indicator to see the health status of women. One of the causes of maternal death is hypertension. Changes in blood pressure of pregnant women can be caused by sleep quality. The type of research used is qualitative. Sampling in this study using non-probability sampling. This research was conducted at the RSUD Indrasari Rengat in 2022 with 89 respondents. Data were collected using a questionnaire and analyzed using the Chi-square test. The sleep quality of pregnant women is mostly poor with a total of 75 people (84.3%). The majority of pregnant women had abnormal blood pressure with a total of 63 people (70.8%). The results of statistical analysis showed p-value = 0.000 (α<0.005). The conclusion of this study is that there is a significant relationship between sleep quality and blood pressure in pregnant women.